North Atlantic Regional Water Resources Study. Appendix S. Legal and Institutional Environment - Henry,Thornton M; Shaw,Peter H (1972)
Contents: Part I - Federal Laws, Policies and Programs; Part II - State Laws, Policies and Programs; and Part III - Interstate-Federal Cooperative Bodies. Appendix S to report dated Jun 72, AD-A036 616. See also Appendix T, AD-A036 625.